الفطريات المنتجة للأفلاتوكسينات في ثمار الزيتون: دراسة على عينات عشوائية مجمعة من الشجرة والمتساقطة على التربة في مناطق مختلفة – ليبيا (Comprehensive Journal of Science, 2026)
This study investigated the fungal diversity and aflatoxigenic potential of fungi associated with olive fruits (Olea europaea) in Tarhuna, Gharyan, and Bin Ghashir, Libya. Samples of tree-attached and naturally fallen fruits were collected between December and February 2024. Identification was performed using morphological and microscopic criteria on Potato Dextrose Agar (PDA). Aflatoxin production was screened using Coconut Extract Agar (CEA) and the ammonia vapor test. Results showed a high prevalence of Aspergillus niger, Aspergillus flavus, Penicillium sp., and Alternaria sp. across all locations. Specifically, A. flavus isolates demonstrated significant aflatoxigenic capacity, indicated by a distinct color change in colony bases upon ammonia exposure. The findings highlight that contamination begins pre-harvest and is exacerbated by soil contact, necessitating strict post-harvest management and toxin monitoring in local olive oil production.
Keywords: Fungi, olive fruits, Aflatoxins, Identification,Isolation